Internal and external loads during hockey 5's competitions among u16 players - Konarski, J. M.; Konarska, A.; Strzelczyk, R.; Skrzypczak, M.; Malina, R. M. (The Journal of Strength and Conditioning Research, 2021)
The purpose of the study was to characterize the external and internal loads associated with Hockey 5's, the modified small-sided format of competition for U16 field hockey introduced in 2014. Subjects were 10 males, 15.2-16.3 years, who were field players on the U16 Polish National Team. A GPSports Athlete Tracking System was used to estimate external loads (sprints, total distance), and a Polar Team2 unit was used to monitor internal loads (heart rate [HR] and energy expenditure [EE]) during active time of play for 8 field players in 2 international matches. Players covered, on average, a distance of 2,217 ± 178 m during a match including 614 ± 12 m sprinting at 8.1 ± 0.8 km/h with a speedmax of 23.1 ± 1.1 km/h. HRmean was 170.5 ± 6.6 b/min, whereas HRmax was 184.9 ± 6.4 b/min. Speed, sprinting, and distance covered did not differ among periods, whereas HR was greater during the second and third periods. HRmax, %HRmax, and EE varied between forwards and defenders, and among periods. Effort expended by field players during Hockey 5's games can be characterized as heavy. The results highlight the need for preparation in both aerobic and anaerobic activities, which include a major speed component and adequate time for rapid recovery to facilitate the adaptation of youth players to the demands of the modified game. Although not directly comparable, comparison of internal loads during Hockey 5's and 11-a-side matches suggests more intensive activity of field players in the former.